Skiing Trauma and Safety: Eighth International Symposium 1991
DOI: 10.1520/stp17638s
|View full text |Cite
|
Sign up to set email alerts
|

A Relative Analysis of Downhill and Cross-Country Ski Injuries

Abstract: This retrospective analysis of cross-country (XC) and downhill (DH) injuries is based on the Consumer Product Safety Commission (CPSC) National Electronic Injury Surveillance System (NEISS) data files and a survey of XC and DH skiing population demographics conducted by the National Ski Retailers Association (NSRA). The study finds that within each sport, the injury population and population at risk demographics are quite similar, but there are significant differences between the two sports in terms of the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The anterior cruciate ligament (ACL) is frequently ruptured during both downhill and cross-country skiing [8,11,12,[14][15][16]19]. Johnson and colleagues [12,14] found that for skiing the type and severity of knee sprains have drastically changed over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) is frequently ruptured during both downhill and cross-country skiing [8,11,12,[14][15][16]19]. Johnson and colleagues [12,14] found that for skiing the type and severity of knee sprains have drastically changed over the last two decades.…”
Section: Introductionmentioning
confidence: 99%